Respon Pertumbuhan Dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) Varietas Bima Brebes Pada Pemberian Pupuk Organik Konsentrat - Debi Hartoni; Nunung Sondari; Endeh Masnenah (Paspalum: Jurnal Ilmiah Pertanian, 2021)
This experiment was carried out in Ujungjaya District, Sumedang Regency. At an altitude of 50 meters above sea level, the soil type is Vertisol. The time of this experiment was carried out from June to August 2020. The purpose of this experiment was to study, determine and get the best dose of growth response and yield of shallot (Allium ascalonicum L.) Bima Brebes variety on the application of concentrated organic fertilizer. The design used was a simple randomized block design (RBD) consisting of 4 treatments of concentrated organic fertilizer in 6 replications. Concentrated organic fertilizers used are: A = 0 g/polybag, B = 50 g/polybag, C = 75 g/polybag and D = 100 g/polybag. The results showed that the application of concentrated organic fertilizer significantly affected plant height, number of leaves at age (14 HST) and tuber weight per plot. The application of concentrated organic fertilizer at a dose of 75 g/polybag showed higher yields on plant height, number of leaves, number of tubers per clump, tuber weight per clump and tuber weight per plot.